THE EFFECT OF FIRST AID EDUCATION FOR CHOKING INCIDENTS IN TOODLERS USING AUDIO-VISUAL MEDIA ON MATERNAL KNOWLEDGE IN THE VILAGE OF BANJARSARI - Enesia Windi Kurniawati; Nurul Fatwati Fitriana (Universitas Kadiri, 2025)
Chocking is an emergency cinfition where there is a blockage of the respiratory airway caused by a foreign object, either partially or completely. The use of video media for the learning process is rapid and easily remembered by respondents because it involves not only hearing but also direct visual engagement through videos. Objective To determine the influence of first aid education on maternal knowledge in handling chocking incidents in toddlers. The study was conducted in Juni 2023 with 75 respondents. Method This study is quantitative research with a pre experimental design using a one group pre test post test approach. The sample consisted of 75 respondents selected through non probability sampling techniques . The research instrument utilized a questionnaire sheet and employed the Wilcoxon test for data analysis. Research results The results of the study showed that the average knowledge score obtained by 75 respondents before receiving audio visual (video) education was 11.64 and after receiving audio visual (video) education, it increased to 18.52. The bivariate analysis using the Wilcoxon test tielded a p-value of 0.001. Conclusion There is an of providing education using audio visual (video) media on maternal knowledge in handling chocking incidents in toddlers in Banjarsari.